39.(27+ (-1))+ 39- ( -27) +35
CÁC BẠN GIÚP MÌNH VỚI
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
25.(27-39)-27.(25-39)
=25x27-25x39-27x25-27x39
=(25x27-27x25)+27.39-25x39
=0+39(27-25)
=0+39x2
=78
Bài 1 :
a) A= (1;2;3;4;5)
b) B= ( 63;64;65;66;67;68;69;70)
Bài 2 :
a) 10x-5 = 11.5-10
10x-5 = 55-10
10x=45+5
10x=50
x=5
b) 27-3x=9.2-3
27-3x = 18-3
27-3x=15
3x=27-15
3x=12
x=4
c) 4x-15=12:12
4x-15=1
4x=16
x=4
d) 2+13x=14.2
13x=28-2
13x=26
x=2
a) \(10x-5=45\)
\(10x=40\)
\(x=4\)
b) \(27-3x=15\)
\(3x=27-15=12\)
\(x=\dfrac{12}{3}=4\)
c) \(4x-15=1\)
\(4x=16\)
\(x=\dfrac{16}{4}=4\)
d) \(2+13x=28\)
\(13x=26\)
\(x=\dfrac{26}{13}=2\)
a) Ta có: \(\dfrac{39}{-65}=\dfrac{-39}{65}=\dfrac{-39:13}{65:13}=\dfrac{-3}{5}\)
\(\dfrac{-3}{5}=\dfrac{-3}{5}\)
Do đó: \(\dfrac{-3}{5}=\dfrac{39}{-65}\)
b) Ta có: \(\dfrac{-9}{27}=\dfrac{-9:9}{27:9}=\dfrac{-1}{3}\)
\(\dfrac{-41}{123}=\dfrac{-41:41}{123:41}=\dfrac{-1}{3}\)
Do đó: \(\dfrac{-9}{27}=\dfrac{-41}{123}\)
c) Ta có: \(\dfrac{-3}{4}=\dfrac{-3\cdot5}{4\cdot5}=\dfrac{-15}{20}\)
\(\dfrac{4}{-5}=\dfrac{-4}{5}=\dfrac{-4\cdot4}{5\cdot4}=\dfrac{-16}{20}\)
mà \(\dfrac{-15}{20}>\dfrac{-16}{20}\)
nên \(\dfrac{-3}{4}>\dfrac{4}{-5}\)
d) Ta có: \(\dfrac{2}{-3}=\dfrac{-2}{3}=\dfrac{-2\cdot7}{3\cdot7}=\dfrac{-14}{21}\)
\(\dfrac{-5}{7}=\dfrac{-5\cdot3}{7\cdot3}=\dfrac{-15}{21}\)
mà \(\dfrac{-14}{21}>\dfrac{-15}{21}\)
nên \(\dfrac{2}{-3}>\dfrac{-5}{7}\)